2021
DOI: 10.20511/pyr2021.v9nspe3.1271
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of BYOD Concept on Development of Learning Process in Universities

Abstract: Education is one of the largest markets promoting implementation of Bring Your Own Device BYOD. The BYOD model was originated in colleges and universities, being stimulated by technologically advanced students, who demanded it, and administrators of educational entities, who agreed that allowance to get access to the network using personal devices was a competitive advantage. Nowadays this concept attracts great attention. People depend on their personal devices and want to have the opportunity to use them any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…BYOD and productivity in education. BYOD (bring your own device) is a practise that can help with teaching and learning and is becoming more popular in the educational sector [43,52]. Research findings on the productivity effect of BYOD in educational institutions revealed that the BYOD intervention had a statistically significant positive effect on students' learning and achievement, as measured by increases in test scores, project quality, and final grades, as well as increased students' motivation, attitudes, and involvement in the course [30,43,53].…”
Section: Byod and Productivitymentioning
confidence: 99%
“…BYOD and productivity in education. BYOD (bring your own device) is a practise that can help with teaching and learning and is becoming more popular in the educational sector [43,52]. Research findings on the productivity effect of BYOD in educational institutions revealed that the BYOD intervention had a statistically significant positive effect on students' learning and achievement, as measured by increases in test scores, project quality, and final grades, as well as increased students' motivation, attitudes, and involvement in the course [30,43,53].…”
Section: Byod and Productivitymentioning
confidence: 99%
“…Media pembelajaran digital tidak terlepas dari peran teknologi yang sedang berkembang pesat. Implementasi BYOD dalam pembelajaran dapat menggunakan perangkat mobile smartphone untuk mendukung kegiatan belajar di dalam ataupun di luar kelas (Sokolova et al, 2021). Mahasiswa dapat menggunakan perangkat milik pribadi atau smartphone dalam pembelajaran (Sánchez et al, 2020).…”
Section: Pendahuluanunclassified
“…O ensino à distância tornase extremamente relevante e independentemente valioso, uma vez que deixa de ser apenas a forma de educação a tempo parcial. O ensino à distância é uma das principais tecnologias 2021). Para estudantes de universidades técnicas, o ensino remoto de uma língua estrangeira é um campo inovador, uma vez que requer atividade orientada para a prática.…”
Section: Introductionunclassified